Antioxidant Activity of Wheat Grass Microgreens (Triticum aestivum L.) with Different Harvest Ages - febrianti, puji febrianti (Jurnal Serambi Biologi, 2023)
Antioxidants are compounds that the body needs to neutralize free radicals and prevent damage caused by free radicals. One drink that is believed to be an antioxidant is wheat grass. Wheat grass is evidence of advances in food science and technology in modifying wheat cultivation techniques using microgreen techniques. This study aims to determine the antioxidant activity of wheatgrass (Triticum aestivum L.) microgreens at different harvesting ages. This research is descriptive. The research was conducted in January-June 2023 at the Biotechnology and Genetics Laboratory, Department of Biology, Padang State University and the Biomedical Laboratory, Faculty of Medicine, Andalas University. The materials used were wheat grass with various harvest ages of 7 days, 10 days and 14 days. Data analysis was carried out using the DPPH method using a microplate reader with a wavelength of 517 nm. The data obtained is presented in the form of pictures, tables and graphs. The results of research on the antioxidant activity of wheatgrass microgreens found very strong activity with an IC50 of 21.798 µg/mL at 10 days of harvest and 14 days of harvest of 14.569 µg/mL. Meanwhile, the harvest age was 7 days with an IC50 of 54.722 µg/mL which was classified as strong.